The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1111/j.1365-2230.1983.tb01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the pharmacokinetics of clobetasol propionate and clobetasone butyrate after a single application of ointment

Abstract: Summary Using new radioimmunoassay methods, the plasma levels of clobetasol propionate and clobetasone butyrate have been measured following application of ointment to in‐patients with psoriasis or eczema. A single application of 25 g of clobetasol propionate 0·05% ointment caused a rapid rise in plasma clobetasol propionate level during the first 3 h. The level fell gradually but was still appreciable 48 h afterwards. Conversely, the plasma cortisol level fell rapidly after application and remained depressed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 12 publications
(5 reference statements)
0
18
0
3
Order By: Relevance
“…used by Hehir et al [3]. As far as we know, other assays for systemic levels of clobetasol propionate have not been published hitherto.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…used by Hehir et al [3]. As far as we know, other assays for systemic levels of clobetasol propionate have not been published hitherto.…”
Section: Introductionmentioning
confidence: 96%
“…The development and validation of a sensitive bioanalytical assay for clobetasol propionate in human serum using LC-triple quadrupole MS is reported hereafter. The topical use of clobetasol propionate leading to low systemic serum levels (approximately 1 ng/ml, 24 h after treatment [3]) particularly demands the high sensitivity of the presented method.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, highly potent topical corticosteroids such as CLO may behave differently since a single application of 20-30 g CLO ointment induces low serum cortisol levels. The biological half-life of CLO is unknown, but it has been shown that cortisol levels remain low until 96 hours after a single application of 25 g CLO in patients with eczema or psoriasis (5). The biological half-life of prednisolone is 12-36 hours (10).…”
Section: Discussionmentioning
confidence: 99%
“…Peak levels of CLO were observed between 6 hours and 9 hours after application. The detection of CLO levels was paralleled by a decrease in cortisol levels reaching a nadir 9 hours after application (5).…”
Section: Introductionmentioning
confidence: 96%